Influence of novel modified waste cooking oil beads on rheological characteristics of bitumen - Elahi, Zafreen; Jakarni, Fauzan Mohd; Muniandy, Ratnasamy; Hassim, Salihudin; Ab Razak, Mohd Shahrizal; Ansari, Anwaar Hazoor (Elsevier, 2024)
The high global need for non-renewable resources such as bitumen for the construction of flexible pavements is a foremost concern in the pavement industry. Thus, researchers are looking for novel approaches such as bio-modifiers to reduce dependency on bitumen. This study investigated the effect of the modified waste cooking oil beads (MWCOBs) as a bio-modifier on the rheological properties, morphological properties, and chemical characteristics. The waste cooking oil (WCO) was pre-processed and modified at two ratios (45:55 and 50:50) with the SBS to form the rubbery material (MWCOBs). The base bitumen (BB) with 60/70 grade was blended with five percentages of MWCOBs for each ratio (5%, 10%, 15%, 20%, and 25%). The results indicated that viscosity has systematically increased with increasing content of MWCOBs and provided a better response at higher temperatures. Adding 5 wt% of MWCOB-A and MWCOB-B improves the viscosities to 513 cp and 562 cp at 135 ℃ respectively compared to 429 cp of BB. The incorporation of the MWCOBSs substantially enhances the elasticity and stiffness of modified bitumens. Additionally, based on the rutting and fatigue parameters, the incorporation of the MWCOBs provides enhanced performance. The 15 A and 15B demonstrated a performance grade (PG) 76 with failing temperatures of 76.2 °C and 78.7 °C respectively. However, 5B exhibited fatigue failure at 13 °C, whereas all other modified bitumens demonstrated fatigue parameter values below 5000 kPa. The separation indices (SIs) based on complex modulus at a temperature of 64 °C of modified bitumen are within the specified range regardless of the 25 A and 25B with SIs of 1.27 and 1.36 respectively. The master curve of 15 A demonstrated higher stiffness at a lower frequency than other bitumen curves and is less stiff at a higher frequency. The field emission scanning electron microscope (FESEM) investigation showed that the MWCOBs are dispersed in the base bitumen and produced a homogeneous matrix. In conclusion, the modified bitumen 15 A and 10B have shown optimal rheological performance and could be utilised as a sustainable bio-modifier.